(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article, based on the analysis of the methods used for drying dried agricultural products, their thermal characteristics are shown and on their basis a combined method of heat supply is developed, as well as a new design of a solar dryer. About the key characteristics and achievements of the solar desiccant and the test results contained therein.